EUROPEAN COURT OF HUMAN RIGHTS, ARTICLE 8 OF THE EUROPEAN CONVENTION ON HUMAN RIGHTS AND RECOGNITION OF SAME-SEX MARRIAGES CONCLUDED ABROAD - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The requirements put before the courts by sources that regulate human rights significantly affect functioning of the mechanism of Private International Law. This statement particularly applies to situations in which it is necessary to give effect to the change of personal and family status acquired abroad. The paper refers to the problem of recognition of same-sex marriages concluded abroad. It analyzes the most important decisions of the European Court of Human Rights regarding the obligation of the member states of the Council of Europe to provide legal protection and recognition to same-sex unions, in accordance with Article 8 of the European Convention on Human Rights (protection of private and family life). The analysis shows that today it is undoubtedly clear that these states have a positive obligation to establish an adequate legal framework that would allow partners in a same-sex union to enjoy certain subjective rights. The obligation in question also extends to same-sex marriages concluded abroad and, when it comes to Serbia, requires immediate legislative intervention.